Uzbekistan and the Eurasian Economic Union (EEU): (is) Integration in the Interests of the Country and the People? - Kh.I.Mominov; I.B.Abdullaev (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2021)
This article analyzes whether or not Uzbekistan join the Eurasian economic union, how beneficial or harmful integration can be for our economy and leading to both positive and negative consequences